Close or positive resection margins are not associated with an increased risk of chest wall recurrence in women with DCIS treated by mastectomy: a population-based analysis - Klein, Jonathan (Springerplus, 2015)
Mastectomy is effective treatment for ductal carcinoma in situ (DCIS) but some women will develop chest wall recurrence. Most chest wall recurrences that develop after mastectomy are invasive cancer and are associated with poorer prognosis. Past studies have been unable to identify factors predictive of chest wall recurrence. Therefore, it remains unclear if a subset exists of women with DCIS treated by mastectomy experience a high rate of recurrence in whom more aggressive treatment may be of benefit. We report outcomes of all women in Ontario (N = 1,546) diagnosed with pure DCIS from 1994 to 2003 treated with mastectomy without radiotherapy and evaluate factors associated with the development of chest wall recurrence. Treatments and outcomes were validated by chart review. Proportional differences were compared using Chi square analyses. Survival analyses were used to study the development of chest wall recurrence in relation to patient and tumor characteristics. Median follow-up was 10.1 years. Median age was 57.1 years. 36 patients (2.3%) developed chest wall recurrence. The 10-year actuarial chest wall recurrence-free survival rates and invasive chest wall recurrence-free survival rates were 97.6 and 98.6%, respectively. There was no difference in cumulative 10 year rates of chest wall recurrence by age at diagnosis (<40 years = 5.2%, 40–44 years = 1.3%, 45–50 years = 2.9%, >50 years = 2.1%; p = 0.19), nuclear grade (high = 3.0%, intermediate = 1.4%, low = 1.0%, unreported = 2.5%; p = 0.41), or among women with close or positive resection margins (positive = 3.0%, 2 mm or less = 1.4%, >2 mm = 1.5%, unreported = 2.8%; p = 0.51). On univariate and multivariable analysis, none of the factors were significantly associated with the development of chest wall recurrence. In this population cohort, individuals treated by mastectomy experienced low rates of chest wall recurrence. We did not identify a subset of patients with a high rate of chest wall recurrence, including those with positive margins.